Downtime Data Center: Memahami Penyebab, Dampak, dan Solusi Efektif - Fahira Sulaiman, Syarifah; Adhitia Hadi Priambodo (Sanskara Manajemen Dan Bisnis, 2024)
This research focuses on the management of downtime risks in Data Centers from a service provider perspective. Utilizing the systematic literature review method, it investigates the impacts of small yet significant downtimes in Data Centers, along with the strategies employed by service providers to address these issues. Key findings highlight that even brief downtimes can lead to substantial financial losses and operational disruptions. Strategies for downtime prevention and recovery are explored, including multi-server optimization, early risk detection, and efficient resource management. This study offers crucial insights for Indonesian Data Center providers to enhance their services and security, aiding them in competing in the global market.